Hypertrophic cardiomyopathy: Translating cellular cross talk into therapeutics - Teekakirikul, Polakit (The Rockefeller University Press, 2012)
Hypertrophic cardiomyopathy (HCM) is a common inherited heart disease with serious adverse outcomes, including heart failure, arrhythmias, and sudden cardiac death. The discovery that mutations in sarcomere protein genes cause HCM has enabled the development of mouse models that recapitulate clinical manifestations of disease. Studies in these models have provided unexpected insights into the biophysical and biochemical properties of mutated contractile proteins and may help to improve clinical diagnosis and management of patients with HCM.